Math

3sqrt(23) * 7sqrt(10) * sqrt(45)

1. 👍 0
2. 👎 0
3. 👁 118
1. 3√23 * 7√10 * √45
3√23 * 7√10 * 3√5
(3*7*3)√(23*2*5*5)
(63)(5√46)
315√46

1. 👍 0
2. 👎 0
posted by Steve

Similar Questions

1. Algebra - sqrts

Square roots. Woohoo. Want to check some work I did. 1. Perform indicated operations 3sqrt+2sqrt-sqrt 3sqrt+2sqrt[3*9]-sqrt[2*6] 3sqrt+3*2sqrt-2sqrt 3sqrt+6sqrt-2sqrt = 7sqrt 2.Simplify

asked by John on November 6, 2007
2. Algebra

Square roots. Woohoo. Want to check some work I did. 1. Perform indicated operations 3sqrt+2sqrt-sqrt 3sqrt+2sqrt[3*9]-sqrt[2*6] 3sqrt+3*2sqrt-2sqrt 3sqrt+6sqrt-2sqrt = 7sqrt 2.Simplify

asked by John on November 6, 2007
3. Pre-Cal(Urgent)

Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were

asked by Hannah on March 29, 2010
4. Pre-Cal

Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were

asked by Hannah on March 29, 2010
5. Pre-Cal

Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were

asked by Hannah on March 29, 2010

Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were

asked by Hannah on March 30, 2010
7. math

3sqrt(7)-3sqrt(64)+7sqrt(112)

asked by ryan on March 31, 2010
8. Math(Roots)

sqrt(24) *I don't really get this stuff.Can somebody please help me? The square root of 24 is 4.898979485566356 I know that..lol,but it says not to use decimals.Here is an example they gave me. Ex.sqrt(18)=sqrt(2*3*3)=3sqrt(2)

asked by Margie... on December 18, 2006
9. Calculus

1) yy'-e^x= 0, and y=4 when x=0 means that: A)y=x-lnx^2+4 B)y^2=4x^2+3 C)y=-2x+1/2x^3 D)y^2=2e^x+14 E)1/2ln|x^2+4|+6 2) The rate of change of P with respect to t is directly proportional to (10-t) and inversely proportional to the

asked by Samantha on May 9, 2014
10. Upper-lower bounds-solved

find the upper and lower bounds for definite integral sign, a=1, b=6, sqrt(x) dx. partitions are as follow: x0=1, x1= 3, x2=6 of the interval [1,6] upper sum: 3sqrt(3) + 3sqrt(6) lower sum: 3sqrt(3) + 3 but this is incorrect. can

asked by Eric on May 15, 2013

More Similar Questions